2022
DOI: 10.1177/08850666221097644
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization and Rehabilitation Practice in ICUs During the COVID-19 Pandemic

Abstract: Background Mobilization and acute rehabilitation are essential in the intensive care unit (ICU), with substantial evidence supporting their benefits. This study aimed to characterize ICU mobilization practices during the COVID-19 pandemic for patients with and without COVID-19. Methods This was a secondary analysis of an international point prevalence study. All ICUs across the world were eligible to participate and were required to enroll all patients in each ICU on the survey date, 27 January 2021. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…The results presented here have important implications both for clinical practice and for the design of future clinical studies of severe COVID-19. Although early rehabilitation for COVID-19 in the ICU has been reported to be both safe and feasible [7,34,35], early rehabilitation may be delayed in the ICU for a number of reasons, all of which are exacerbated by sta ng shortages and infection control, overwhelmed hospital capacity, and the obesity status and severity of respiratory failure of patients. In the present study, prolonged IMV was signi cantly associated with longer time to rst mobilization and LOS in the ICU, suggesting that new interventions, such as electrical muscle stimulation therapy, should be implemented in the ICU to prevent functional decline in patients with severe COVID-19 [36].…”
Section: Discussionmentioning
confidence: 99%
“…The results presented here have important implications both for clinical practice and for the design of future clinical studies of severe COVID-19. Although early rehabilitation for COVID-19 in the ICU has been reported to be both safe and feasible [7,34,35], early rehabilitation may be delayed in the ICU for a number of reasons, all of which are exacerbated by sta ng shortages and infection control, overwhelmed hospital capacity, and the obesity status and severity of respiratory failure of patients. In the present study, prolonged IMV was signi cantly associated with longer time to rst mobilization and LOS in the ICU, suggesting that new interventions, such as electrical muscle stimulation therapy, should be implemented in the ICU to prevent functional decline in patients with severe COVID-19 [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another aspect to consider and that could have important negative effects on the subsequent functional recovery of ICU and COVID-19 patients is the lack of mobilization during hospitalization. In this regard, a study by Liu et al (2022) 141 conducted with data from 135 ICUs, with a total of 1,229 patients in 33 countries around the world, showed that more than 90% of patients with MV (positive or negative for COVID-19) during the pandemic, remained completely immobile most of the time. These results are worrying considering the enormous number of sequelae that these patients can have and, without a doubt, it is essential to change the therapeutic approach to one where mobility is a fundamental element of the rehabilitation.…”
Section: Treatment Of Icu-acquired Weakness In Covid-19 Patientsmentioning
confidence: 99%
“…These results are worrying considering the enormous number of sequelae that these patients can have and, without a doubt, it is essential to change the therapeutic approach to one where mobility is a fundamental element of the rehabilitation. 141 Regarding post-ICU rehabilitation in COVID-19 patients, given the limited information, more research is needed. 139,142 Patients with physical function sequelae of ICU-AW and COVID-19 need physical therapy to reverse the disability associated with cardiopulmonary dysfunction and muscle atrophy.…”
Section: Treatment Of Icu-acquired Weakness In Covid-19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only did patients with COVID-19 experience lengthy admissions in 2020, many also had prolonged periods of ventilator dependence and associated immobility. 10 Due to high comorbidity burden, most patients receiving maintenance dialysis require greater time and support to recover from a prolonged admission; in the meantime, hospital-acquired frailty increases their vulnerability to future illness and complications, 11 even after recovery from COVID-19 itself.…”
mentioning
confidence: 99%